Polyphasic characterization of rhizobial isolates obtained from different common bean-producing regions (Bioscience Journal, 2023)
In Brazil, the common bean is a crop with significant social and economic importance. The prospecting of N2 fixing bacteria is crucial since biological nitrogen fixation (BNF) is an eco-friendly technique.  This work aimed to obtain and characterize rhizobium isolates based on morpho-physiological, molecular, and symbiotic efficiency parameters, using the strains SEMIA 4077, SEMIA 4080, and SEMIA 4088 as references. The characteristics of the isolates and colonies, their tolerance to salinity and temperature, as well as their utilization of carbon sources, served as the basis for the morpho-physiological characterization. BOX-PCR, REP-PCR, and ERIC-PCR markers were used for genotypic characterization. Assessment of the symbiotic efficiency was carried out in a greenhouse, determining the number of nodules (NN), nodule dry weight (NDW), shoot dry weight (SDW), and total-N (Total-N) accumulation in the shoot. Among the isolates, those exhibiting: neutral culture medium pH, fast growth, colony diameter